2012
DOI: 10.1016/j.matchemphys.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of high concentrated aqueous silver nanofluid and inkjet printing on ceramic substrates

Abstract: In this paper, the formulation of a high Ag loading (45 wt %) aqueous ink and its subsequent printing on three different ceramic substrates were reported. Monodispersed Ag nanoparticles with a size down to 10 nm were successfully synthesized in aqueous medium. These nanoparticles were then successfully dispersed up to 45 wt% in aqueous medium with the aid of a co-polymer, Pluronic F127. The printed tracks show the electrical conductivity of 3μΩcm close to the value of silver bulk (1.6 μΩcm). The use of high so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 14 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…Kosmala et al 19 reported inkjet printing of silver ink with a solid loading up to 45 wt % to achieve thick conductive lines for low resistance. Ahn et al 20 used highly concentrated (>70 wt %) silver ink for a direct ink writing method for omnidirectional (3D) printing of fine and high aspect ratio silver lines.…”
mentioning
confidence: 99%
“…Kosmala et al 19 reported inkjet printing of silver ink with a solid loading up to 45 wt % to achieve thick conductive lines for low resistance. Ahn et al 20 used highly concentrated (>70 wt %) silver ink for a direct ink writing method for omnidirectional (3D) printing of fine and high aspect ratio silver lines.…”
mentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1355-2546.htm Traditional glass (Hrehorova et al, 2011;Pajor-Swierzy et al, 2019), plastic (Farraj et al, 2017;Michael Grouchko, 2011;Rosen et al, 2019), paper (Zhang et al, 2019;Xu et al, 2013;Kant et al, 2020), ceramic (Kosmala et al, 2012) and textile (Hu et al, 2010; can be used as circuit materials. Circuit patterns printed on paper have obvious advantages such as low cost, portability, environmental protection and recyclability.…”
Section: Research Background and Significancementioning
confidence: 99%
“…The formulation of aqueous inks with suspended nanoparticles has already been successfully demonstrated for Ag colloids [17,18]. In particular, stable inks with a solid loading up to 45 % wt of Ag nanoparticles were prepared with the aid of a polyethilenoxide-polypropilenoxide copolymer [17].…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of aqueous inks with suspended nanoparticles has already been successfully demonstrated for Ag colloids [17,18]. In particular, stable inks with a solid loading up to 45 % wt of Ag nanoparticles were prepared with the aid of a polyethilenoxide-polypropilenoxide copolymer [17]. On the other hand, inkjet printing of several metal oxide nanoparticles (Al2O3, TiO2, WO3) was reported to be more challenging [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%